Islamic ethics towards refugee: Reflections on the responses of Muslim-majority countries - Islam, Md Thowhidul (IIUC Studies, 2026)
The issue of ‘Refugee’ has become a pressing global concern, with thousands displaced every year, the majority of whom are Muslims. According to UNHCR (2021), 89.3 million people worldwide are displaced, including 27.1 million refugees, primarily from Afghanistan, Myanmar, South Sudan, and Syria. Many live under inhumane conditions. In Islamic thought, hijra (migration) provides a broader understanding of asylum, recognizing it as a fundamental right irrespective of religion. The Holy Qur’an instructs Muslims to protect those seeking refuge, while both the Qur’an and Hadith establish a normative framework for safeguarding refugee rights. Against this backdrop, the study critically examines how Muslim-majority countries have responded to refugee challenges from an Islamic ethical perspective. Employing a critical review of literature, data analysis, and secondary sources such as books, journals, and official reports, it explores the gap between Islamic ethical obligations and state practices. The study also offers policy recommendations to enhance refugee protection and dispel prevailing misconceptions. IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 41-66